Obstacles to creative teaching among Arabic language teachers at the primary level in Medina (from their point of view) - Aljehni, Taghreed Muslim Ateeq; Alofi, Ibrahim Awadhallah Raja (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the obstacles to creative teaching among Arabic language teachers at the primary school in Madina from their point of view. In order to achieve the goal, the researcher used the descriptive survey method. The researcher designed a questionnaire, that consisted of (29) items. The research sample was (328) male and female teachers, who were chosen by simple random method. the researcher found the following results: The axis of constraints related to the school environment came first, with an arithmetic mean (3.98) and The axis of student’s constraints ranked second, with an arithmetic mean (3.46), and The axis of obstacles related to the textbook came in third place with an arithmetic mean (3.49) and The axis of the teacher’s obstacles ranked fourth and last in terms of verbal significance (medium) with an arithmetic mean (3.34) and There are no statistically significant differences at the level of significance (0.05) between the average responses of the sample members to the degree of severity of the creative teaching obstacles related to (the teacher and the textbook) in addition to the obstacles to creative teaching as a whole due to the gender variable. There are differences in the two axes (school environment, student) due to the variable of sex in favor of males (teachers). There are no differences in (obstacles specific to the teacher, obstacles specific to the textbook, obstacles for the student) in addition to obstacles to creative teaching as a whole, due to the variable of years of experience. However, there are differences in the axis (obstacles related to the school environment) due to the variable of years of experience, in favor of those with experience (5-10) years, and those with experience (more than 10 years) over those with less than (5 years) experience only.